A COMPREHENSIVE ANALYSIS OF CANNABIS’S THERAPEUTIC POTENTIAL IN RELATION TO THE HUMAN BODY - JEEVANANTHAM I; PAVISH KUMAR K; MICAH ISAAC ANAND W; DHYANESH R; SYED MOHAMED OMAR; JEYARAM BHARATHI JEYABALAN (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Cannabis has emerged as a subject of intense scientific interest due to its multifaceted therapeutic potential across a broad spectrum of human physiological and pathological conditions. This comprehensive analysis explores the pharmacological properties, therapeutic applications, and mechanistic insights of cannabis and its bioactive constituents, primarily cannabinoids such as delta-9-tetrahydrocannabinol and cannabidiol, to the human endocannabinoid system. The manuscript delves into the roles of cannabis in pain modulation, neuroprotection, inflammation, psychiatric disorders, oncology, and gastrointestinal and metabolic disorders, supported by both pre-clinical and clinical findings. Emphasis is placed on the interaction between cannabinoids and cannabinoid receptors (CB1 and CB2), as well as non-cannabinoid targets, illustrating the systemic effects of cannabis on homeostasis and disease modulation. While the therapeutic promise of cannabis is compelling, the analysis also highlights the challenges posed by dosage standardization, psychoactive side effects, legal restrictions, and limited long-term safety data. This review underscores the necessity for rigorous, evidence-based research and regulatory frameworks to unlock the full medicinal potential of cannabis while ensuring patient safety and therapeutic efficacy.